591 SEQUENCE OF DIAGNOSTIC TESTING IN CARDIAC AMYLOIDOSIS: EARLY MONOCLONAL PROTEIN STUDY IS ASSOCIATED WITH BETTER OUTCOMES IN AL AMYLOIDOSIS. (15th December 2022) - Milani, Paolo; Fabris, Francesca; Mussinelli, Roberta; Obici, Laura; Nanci, Martina; Basset, Marco; Benvenuti, Pietro; Bellofiore, Claudia; Nuvolone, Mario; Foli, Andrea; Perlini, Stefano; Rapezzi, Claudio; et al.
Abstract: Background: Isolated cardiac amyloidosis (CA) is a complex diagnostic scenario, highlighting the need for physician awareness in differential diagnosis. Among the different types of amyloidosis, nearly all cases of CA are caused by light chain (AL) and transthyretin amyloidosis (ATTR). Patients with suspect CA without monoclonal components (MC) in both serum and urine and normal free light chain (FLC) ratio can have a non-biopsy diagnosis of ATTR amyloidosis with bone scintigraphy (1). However, in all suspected CA with a MC (approximately 20% of patients with ATTR amyloidosis), amyloid typing is mandatory. Thus, the diagnostic pathway of CA diverges based on MC-studies. We aim to assess if different sequence of diagnostic tests can affect outcomes in patients with cardiac AL amyloidosis. Methods: Pavia Amyloidosis prospectively maintained database was searched for patients with isolated cardiac AL amyloidosis referred to our Centre from January 2016 to December 2020. Patients with a known monoclonal gammopathy (MG) and with multiple organ involvement were excluded. We searched for the date of symptom onset and first suspect of CA (i.e. recognition of clinical, imaging or laboratory signs of CA). In addition, we recorded the date of the different diagnostic tests performed: i.e. echocardiogram; serum and urine immunofixation and FLC measurement (MC-study); bone scintigraphy and cardiac magnetic resonance (defined as advanced cardiac imaging). We calculated the interval between those time-points and the final diagnosis: (a) from symptom onset to diagnosis, (b) from first suspect to final diagnosis, (c) from first suspect to MC-study and (d) to advanced cardiac imaging tests. We then searched for possible intervals of time amongst those, that were able to predict death at 3 months, by means of a ROC analysis. Results: A total of 94 patients were included in the analysis (25% of all patients with cardiac AL amyloidosis diagnosed in the study period). Six (6%) patients died <1 month from diagnosis, and 27 (29%) died <3 months. Median overall survival (OS) of the whole cohort was 8 months, and the median follow-up of living patients was 39 months (range 16-73). The median time from symptom onset to diagnosis was 9 months (range 1-44) and the median time from the first suspect to diagnosis was 2 months (range 0-9). An interval from the first suspect to MC-study ≥6 weeks was the only predictor of death at 3 months. None of the other tested periods were associated with a significant ability to predict survival. A delay in MC-study ≥6 weeks identified patients with more advanced cardiac stage (50% vs. 25% were stage IIIb, P=0.02) and was associated with a significantly worse outcome (median survival 13 months vs. 4 months, P=0.012). In the whole cohort, a total of 76 (81%) patients underwent at least one advanced imaging examination. Amongst those, 37 (49%) performed the imaging tests before MC-study with a higher percentage of patients who had a delay in MC-studies evaluation (69% vs. 27%; P<0.001). Conclusion: In patients who present with isolated cardiac AL amyloidosis with previously unknown MG, a relatively short delay in identifying the amyloid MC results in a considerable reduction of survival. A delay in MC-study was associated with more advanced cardiac stage. MC studies should be the first step in the work-up of patients with suspected CA to guide biopsy vs. non-biopsy diagnostic approach.